Crop of the Middle Urals in 1913-2012: One Hundred Years of Reforming - V. N. Mamyachenkov (Научный диалог)
The article is devoted to the subject insufficiently developed in the domestic historiography, especially in regard to its regional dimension. The study is conducted on materials of the Centre of documentation of public organizations of Sverdlovsk region with the assistance of the scientific and publicistic literature. The relevance of the topic is determined by its high importance for the social sciences, especially for history. Scientific novelty of the work is seen in the fact that the new materials discovered by the author in these archives are introduced into scientific usage. The purpose of writing the article was to identify the certain stages of the history of Middle Urals crop production, its characteristic features and problems of growth and efficiency that had to be solved by the workers in this sector of the economy. It is noted that the importance of the crop to the economy of mankind is difficult to overestimate. It is argued that the periodization of the history of plant cultivation in the Middle Urals can be carried out on several grounds. It is claimed that a great help in the reasoning and conclusions of the article provided statistics on the growing region in the investigated period summarized in several tables. It is stated that the urbanization in Russia and the Soviet Union proceeded much more painfully than in Western countries, as occurred against the backdrop of a significant lagging of the country in socio-economic development. It is declared that the degradation of the planting was shown up, primarily, in a rather significant reduction of crops of most plants. It is emphasized that the authorities, especially since the 1960-ies, were trying in some way to improve the efficiency of agriculture and crop production. It is proved that the effect from the huge public investment was clearly inadequate and disproportionate: agriculture absorbed huge funds at low returns. The conclusion is that, despite the much more advanced modern agricultural technologies and the transfer of the agricultural sector on a market basis of functioning, one can’t talk about any significant progress in crop production in the region.